2020
DOI: 10.1001/jamacardio.2020.2795
|View full text |Cite
|
Sign up to set email alerts
|

Survival on the Heart Transplant Waiting List

Abstract: IMPORTANCE With continuing improvements in medical devices and more than a decade since the 2006 United Network for Organ Sharing (UNOS) allocation policy, it is pertinent to assess survival among patients on the heart transplantation waiting list, especially given the recently approved 2018 UNOS allocation policy.OBJECTIVES To assess survival outcomes among patients on the heart transplant waiting list during the past 3 decades and to examine the association of ventricular assist devices (VADs) and the 2006 U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
41
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 13 publications
0
41
0
Order By: Relevance
“…During this time, there was a significant increase in 1-year survival on the HT waiting list from 34.1% in 1987-1990 to 67.8% in 2011-2017. 25 While this finding correlates with a definite increase in ICD implantation over this time period, the decrease in waitlist mortality is likely also contributed by improvement in heart failure management with the introduction of temporary MCS and the evolution of LVADs. 26,27 As mentioned previously, early studies of ICD use in HT candidates only showed a survival benefit in patients implanted for secondary prevention.…”
Section: Survival Benefit Of Icd Implantation In Patients Awaiting Htmentioning
confidence: 83%
“…During this time, there was a significant increase in 1-year survival on the HT waiting list from 34.1% in 1987-1990 to 67.8% in 2011-2017. 25 While this finding correlates with a definite increase in ICD implantation over this time period, the decrease in waitlist mortality is likely also contributed by improvement in heart failure management with the introduction of temporary MCS and the evolution of LVADs. 26,27 As mentioned previously, early studies of ICD use in HT candidates only showed a survival benefit in patients implanted for secondary prevention.…”
Section: Survival Benefit Of Icd Implantation In Patients Awaiting Htmentioning
confidence: 83%
“…A final consideration during the pre-transplant period is the donor. Donor organs remain scarce and HT waitlist mortality remains significant [ 40 ]. This organ scarcity and ethical concerns about allocating organs to older recipients is reflected in the 2016 ISHLT Listing Criteria for HT which specify that for carefully selected patients over 70 years of age who are considered for HT, an alternate-type program be considered [ 25 ].…”
Section: Pre-transplant Considerations For Older Adultsmentioning
confidence: 99%
“…Transplant programs have looked to extend donor organ utilization using novel means to rehabilitate organs both before and after procurement. 1,2 For suitable donors, procurement of multiple organs is an invaluable way to increase the number of potential recipients who may benefit from a single donor. The technique of procurement of an isolated heart differs from the technique of procurement of both heart and lungs, and little comparative data have been published regarding the longand short-term outcomes after transplantation of a heart from an isolated heart (IH) donor versus a combined heart-lung (CHL) donor.…”
mentioning
confidence: 99%